Preparation and Physiological Activity of Carboxymethylated Siraitia grosvenorii Polysaccharide with Different Degrees of Substitution - Guizhen LIU; Zhiwei YANG (Shipin gongye ke-ji, 2023)
To investigate the effect of carboxymethylated with different degrees of substitution on the properties of Siraitia grosvenorii polysaccharide (SGP), carboxymethylated Siraitia grosvenorii polysaccharide (CSGP) was prepared by solvent method by using the raw material of SGP. The effects of chloroacetic acid concentration, reaction time, and sodium hydroxide concentration on the degree of substitution were analyzed, and the CSGP with the degree of substitution ranging from 0.28 to 1.09 was prepared. The physicochemical properties of CSGP with different substitution degrees were characterized, and the effects of substitution degrees on hypoglycemic activity and antioxidant activity were investigated by in vitro physiological activity experiments. The high-performance gel permeation chromatography revealed that the molecular mass of CSGP was smaller than that of SGP. The results of FTIR manifested a new absorption peak at 1317 cm−1, indicating that carboxymethyl was successfully introduced into the polysaccharide. The results of scanning electron microscopy showed that with the increase of substitution degree, the surface morphology of CSGP became more fragmented and appeared to curl. Congo red experiment revealed that the triple helix structure of CSGP with high substitution degree disappeared. In vitro physiological activity experiment showed that 6 mg/mL of the CSGP-M had the highest α-amylase inhibition, DPPH, and hydroxyl radical scavenging rates of 44.36%±1.30%, 63.17%±2.07%, and 70.21%±1.89%, respectively. Compared with SGP, CSGP-L and CSGP-H, CSGP-M with medium degree of substitution has the best hypoglycemic activity and antioxidant activity in vitro. When the degree of substitution was increased to 1.09, the inhibition rate of α-amylase, DPPH and hydroxyl radical scavenging rate of CSGP-H decreased to 11.65%±0.26%, 47.45%±0.79%, and 34.85%±0.78%, respectively. The results indicated that CSGP with medium degree of substitution could exert the best physiological activity.